The Role of Women Leadership in India's Politics and Government: A Factual and Fictional Analysis of ‘The Last Queen’ by Chitra Banerjee - Kolukuluri, Sr.Vimala Devi; Vijayanand, Dr. A. (The journal of contemporary issues in business and government, 2023)
In the modern time, women in India were given freedom of expression and equality as well as right to be educated. They were enjoying the 'Ladies first' facility in different fields as they were holding numerous prestigious positions during this era. A strong woman is not born down by adversity, she knows how to turn her pain into her greatest strength woman makes a stupendous personal sacrifices, woman is a Icon of Liberation. A woman is a pearl of great prize. The book of “last Queen” is the tale of woman told by a woman enlivens the vastly unknown story of Jindan by intriguingly blending fact and fiction into an unputdownable novel. The last Queen portrays a simple village girls and her transition to the last queen of Maharaja Ranjit Singh. It is a timeless tale of a lady, which excites the reader with a spirit of patriotism and bravery. Divakaruni blends in Jindan the attributes of a girl-next-door and an magnanimous queen who is rooted, intelligent, who bows to no external force, but have passionate love for Punjab.